PELATIHAN DAN PENDAMPINGAN PENGOLAHAN CABAI RAWIT MENJADI BUBUK CABAI SIAP KONSUMSI DI KELOMPOK TANI PANGAN SEJAHTERA SARWA PRANI KELURAHAN PENATIH DENPASAR TIMUR - I Wayan Budi Satriya; Ni Kadek Gita Purnamasari (UNHI Press, 2021)
The farmer group Pangan Sejahtera Sarwa Prani is a farmer group located in Penatih Village, East Denpasar District, Denpasar City. From its establishment in December 2020 until September 2021, this farmer group has succeeded in harvesting several food crops, one of which is cayenne pepper. As with most food crop commodities, problems arise when the harvest season arrives, the abundance of crops and crop durability are the main problems faced by farmers. These problems will force farmers to immediately sell their harvests even at low prices, therefore training on post-harvest processing of cayenne pepper into chili powder ready for consumption can be an alternative solution to the problems faced. This training activity was carried out within the framework of the 2021 Indonesian Hindu University Real Work Lecture and Community Service which was attended by eight participants consisting of members of the farmer group and PKK in Central Tembawu, Penatih Village, East Denpasar. This training activity show if processing of cayenne pepper into chili powder can be a solution to the problem of durability of post-harvest cayenne pepper and on the other hand, can increase the added value of the cayenne pepper harvest in the Pangan Sejahtera Sarwa Prani Farmers Group.